Implementasi Chatbot Berbasis Aturan untuk Layanan Customer Service E-commerce pada Platform WhatsApp - Surya Rizky Maulana Ibrahim; Dede Handayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The high intensity of repetitive questions regarding product information, order status, and store policies in e-commerce businesses creates an additional workload for customer service and delays responses to customers. This research aims to implement a rule-based chatbot on the WhatsApp platform to automate customer service. The method used is the Waterfall software engineering model with stages of needs analysis, design, implementation, testing, and evaluation. The chatbot was implemented using Python integrated with WhatsApp Business API utilizing quick reply features. Functional testing results on 100 question samples show 87% accuracy. Usability testing using the System Usability Scale (SUS) on 30 users yielded a score of 78.5 (category